Tussilagone Suppresses Angiogenesis by Inhibiting the VEGFR2 Signaling Pathway - Li, Jia; Peng, Jiangtong; Zhao, Shengnan; Zhong, Yi; Wang, Yilong; Hu, Ji; Zhang, Chao; Cheng, Min; Xia, Geqing; Hu, Yu; Huang, Kai; Wang, Yan; et al. (Frontiers in Pharmacology, 2019)
Tussilagone (TSL) is a sesquiterpenoid isolated from Tussilago farfara, which has been used as a traditional medicine for the treatment of asthma and bronchitis. It also takes part in the anti-inflammatory and antioxidant effects, but its role in angiogenesis is unknown. Angiogenesis is a cancer feature that is essential for supplying oxygen and nutrients to all proliferating tumor cells. Here, we demonstrated that TSL significantly inhibited the proliferation, migration, invasion, tube formation of primary human umbilical vascular endothelial cell (HUVEC) in vitro. And TSL inhibited VEGF-induced angiogenesis revealed by Matrigel plug assay in vivo. Meanwhile, we observed that TSL inhibited the activity of VEGFR2 signal pathway induced by VEGF. These findings suggested that the TSL may serve as a potential therapeutic target in the angiogenesis.